The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/md.0000000000009023
|View full text |Cite
|
Sign up to set email alerts
|

The role of stereotactic body radiation therapy in oligometastatic colorectal cancer

Abstract: Rationale:Regorafenib is the new standard third-line therapy in metastatic colorectal cancer (mCRC). However, the reported 1-year overall survival rate does not exceed 25%.Patient concerns:A 55-year-old man affected by mCRC, treated with regorafenib combined with stereotactic body radiotherapy (SBRT), showing a durable response.Interventions:After 6 months of regorafenib, a PET/CT scan revealed a focal uptake in a solid lung nodule which was treated with SBRT, whereas continuing regorafenib administration. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography-computed tomography (PET/CT) has been widely used in the diagnosis, staging and therapeutic evaluation of various malignancies. [16,17] Also, the prognostic prediction value in PDAC was reported by several researchers. [1820] For resected PDAC patients, 18 F-FDG PET/CT metabolic parameters maximum standardized uptake values (SUVmax), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were illustrated to strongly correlate with OS and progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…The 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography-computed tomography (PET/CT) has been widely used in the diagnosis, staging and therapeutic evaluation of various malignancies. [16,17] Also, the prognostic prediction value in PDAC was reported by several researchers. [1820] For resected PDAC patients, 18 F-FDG PET/CT metabolic parameters maximum standardized uptake values (SUVmax), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were illustrated to strongly correlate with OS and progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…SBRT with regorafenib. An mCRC patient with liver metastases taking regorafenib who also received SBRT experienced a durable progression-free survival over 3 years [6]. SBRT monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the optimal timing, duration, and dosing of regorafenib when used in combination with RT or SBRT remain unknown. Roberto et al [ 15 ] reported a man affected by metastatic colorectal cancer (mCRC) who was treated with regorafenib combined with multiple fractions of SBRT with 54 Gy, achieving a durable response without severe toxicities. Gatto et al [ 33 ] also reported a patient affected by metastatic gastrointestinal stromal tumor who was treated with RT (34 Gy in 14 fractions) combined with regorafenib (160 mg/day), achieving an objective response.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a patient was reported to have developed transverse myelopathy from regorafenib two years after receiving SBRT for metastatic liver lesions [ 14 ]. However, a colon cancer patient who received regorafenib and concurrent SBRT for an oligometastatic lung nodule showed an impressive response [ 15 ]. The treatment or toxicities of regorafenib with RT have different expressions in the concurrent or sequential regimen.…”
Section: Introductionmentioning
confidence: 99%